The role of experiential value in mediate experiential marketing on repurchase intention - Darmawan, Made Harry; Yasa, Ni Nyoman Kerti (International research journal of management, IT and social sciences, 2022)
The various types of culinary businesses offered are so diverse such as restaurants, cafes, lounges, and bars. One local restaurant that is well known to the public is MM Juice and Restaurant. An indicator of the success of a company is determined by the intention to repurchase its consumers on an ongoing basis which is one of the factors that MM Juice and Restaurant want to improve. This study aims to explain the role of experiential value in mediating the effect of experiential marketing on repurchase intention. This research was conducted in Denpasar City involving 185 respondents who live in Denpasar with an age range of 18 years and over and have completed high school education. The method used is online purposive sampling via Google Form. The data analysis technique used is a descriptive statistical analysis technique, path analysis, and Sobel test. The results of this study indicate that experiential marketing has a positive and significant effect on experiential value.